Recovery Process of Condensate the Ammonia Wastewater Plant of PT.PIM with A Combination of Technology Air Stripping Jet Bubble Colum, Advance Oxidation process and Ion Exchange Resin - Nur, Muhammad; Munawar, Edi; Mariana, Mariana (Jurnal Rekayasa Kimia & Lingkungan, 2017)
AbstractStudy of reducing the content of ammonia, carbon dioxide and organic contaminants in wastewater process condensate using a combination of technologies of water Jet Stripping Bubble Colum, Advance Oxidation Process and Ion Exchange Resin have been done. The aims of this research is to look the effect of hydraulic resident time in Jet Stripping Bubble Colum and the amount of the addition of Ozon/H2O2 to reduction the content of carbon dioxide and organic contaminants as well as ammonia removal with ion exchange resin on the process condensate so that can be reuse as boiler feed water in ammonia plant of PT. PIM. This research was conducted using a combination Air Stripping Jet Bubble Colum, Advance Oxidation Process and Ion Exchange Resin which equipped with water and air flows adjustment. The water flow enter the column, pressure of the Colum and diameter of nozzle was maintained constantnts during experiment, while the air flow rate enter to the column, H2O2/O3 concentrations and the hydraulic retention time was vary respectively. The results showed that the water Jet Stripping Bubble Colum at 50 Psi air pressure capable of achieving CO2 lowers 87.60% and ammonia to 65.31%. AOP technology capable of lowering the content of organic contaminant to 80.71% with the addition of hydrogen peroxide 8,000 ppm with a residence time 180 minutes. While the ammonia remaining in the water the process of condensate action exchange resin using eliminated with a reduction of ammonia reached 98.57%, so that the recovery process of water condensate technology uses a combination of Air Stripping Jet Bubble Colum, Advance Hydrocarbon processes (AOP) and Ion Exchange Resins already meets the requirements of viable reuses boiler feed water. The ammonia reduction was determined by using ASTM-D 1426 method, the carbon dioxide by using ASTM-512 method, and the organic contaminants by using titrimetric method (SII-0071).Keyword : Air Stripping Jet Bubble Colum, Advance Oxidation Process (AOP), Ammonia Removal, Carbon Dioxide Removal.